Reflections on life-course vaccination: the England experience. (13th November 2019) - Edelstein, M
Abstract: Since the introduction of the expanded programme on immunization in the 1970s, vaccination has evolved from being an intervention of early infancy to being a programme targeting individuals at all stages of life including birth, infancy, childhood, teenage years, pregnancy and adulthood. The UK has been at the forefront of this lifelong approach to vaccination and has introduced vaccines at all stages of life in its national schedule, including vaccination against hepatitis B at birth, Meningococcal disease group B in infancy, influenza in primary school years, Meningococcal disease groups A, C, W and Y in teenage years, pertussis in pregnancy and shingles in older adults. Based on a range of studies conducted by Public Health England, This session will reflect on some of the challenges brought on by the life course approach in the UK including issues of access in different age groups, choosing the right age and settings for vaccinations, age-specific attitudes to vaccination and subsequent communication strategies, and challenges with monitoring a life-course programme.